2012
DOI: 10.3382/ps.2011-01675
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance and histological features of intestinal mucosa of broiler chickens fed different dietary protein levels

Abstract: To evaluate the effect of decreasing dietary protein on growth performance, carcass traits, and intestinal mucosal morphometry, 180 female Hubbard strain broiler chickens were divided into 3 groups and fed 3 isoenergetic diets ad libitum from 14 d of age until slaughter age (49 d). The treatments varied according to 3 protein levels: high-protein diet (HiP, 22.5% CP, DM basis), medium-protein diet (MedP, 20.5% CP), and low-protein diet (LowP, 18.5%). Diets were obtained by replacing wheat middlings with soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
152
2
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(181 citation statements)
references
References 26 publications
18
152
2
9
Order By: Relevance
“…Other researchers report no morphological changes at doses of 500 mg of oregano oil per kg of feed (Onderci et al 2008, Betancourt et al 2012, Emami et al 2012, Laudadio et al 2012, Wu et al 2013. Olnood et al (2015) mentioned that additives could favor the development of bacteria and improve growth of the anatomical structures.…”
Section: Height Of Intestinal Villimentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers report no morphological changes at doses of 500 mg of oregano oil per kg of feed (Onderci et al 2008, Betancourt et al 2012, Emami et al 2012, Laudadio et al 2012, Wu et al 2013. Olnood et al (2015) mentioned that additives could favor the development of bacteria and improve growth of the anatomical structures.…”
Section: Height Of Intestinal Villimentioning
confidence: 99%
“…The main function of the villi is the absorption of nutrients, an activity which is partially dependent on its size. In addition, villi can be considered as intestinal health indicator (Uni et al 1998, Laudadio et al 2012. Natural additives improve the epithelium surface structure and increase the enterocytes size Peng 2008, Incharoen et al 2010).…”
Section: Height Of Intestinal Villimentioning
confidence: 99%
“…Previously, some of the authors have reported improved reproductive performance by feeding lower protein levels in male broiler breeders (Zhang et al 1999;Romero-Sanchez et al 2007). Similarly, Laudadio et al (2012) recently found that a lower protein level (20.5%) is a better choice for optimum level of growth in broilers than a higher protein level (22.5%). In all these reports, the antioxidants' status of the birds has not been measured; however, it is inferred that the improved performance achieved with the lower level of protein may have some association with enhanced anti-oxidant status, which needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Lactobacillus and Bifadobacterium have been reported to improve the anti-oxidant status in birds (Sohail et al 2011) by decreasing the production of free radicals (Fuller 1989). The lower levels of crude protein (CP) control body weight gain and decrease blood urea, which is translated into improved reproductive performance of the birds (Zhang et al 1989;Romero-Sanchez et al 2007;Laudadio et al 2012). Some authors have indicated that different levels of dietary protein may affect the serum antioxidants in poultry (MachIn et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the adequate level of protein is favorable both for the bird, which might perform its metabolic functions in a potentiated way, as well as for the producer, who might maximize its financial resources through saving with protein sources (Sakomura et al, 2002;Laudadio et al, 2012a;Laudadio et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%